Pengaruh Kemampuan Finansial, Literasi Keuangan, Dan Risk Tolerance Terhadap Minat Investasi Mahasiswa Di Pasar Modal (Studi Pada Mahasiswa Jurusan Akuntansi Universitas Warmadewa) - A.A. Istri Citra Dewi; Sang Ayu Putu Arie Indraswarawati; Putu Cita Ayu (UNHI Press, 2026)
The Indonesian capital market plays a key role in supporting national development by providing funding for various sectors. This study aims to evaluate the impact of financial ability, financial literacy, and risk tolerance on students' investment interest in the capital market. The research was conducted on seventh-semester Accounting students of the Faculty of Economics and Business at Warmadewa University, with a sample of 180 respondents selected using the Slovin formula. Data were collected through questionnaires and analyzed using multiple linear regression. The results of the study indicate that financial ability, financial literacy, and risk tolerance have a positive and significant effect on students' investment interest. Among these three factors, risk tolerance is the most influential factor on investment interest. These findings highlight the importance of improving financial literacy, good personal financial management, and the development of a brave and wise investor character in facing market risks.